1972
DOI: 10.1002/pol.1972.160100808
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of submicrocrack generation in stressed polymers

Abstract: SynopsisSubmicrocracks, free radicals, and endgroups of scissioned molecules formed in polyethylene, polypropylene, and polycaprolactam under uniaxial tension have been investigated. Measurements were carried out by small-angle x-ray scattering, electron paramagnetic resonance, and infrared spectroscopy. The concentration of submicrocracks is almost the same as that of free radicals but is smaller than the concentration of scissioned macromolecules by approximately three orders of magnitude. The number of scis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 8 publications
2
65
1
1
Order By: Relevance
“…Only a very small increase of the equatorial intensity is observed limited to the smaller angles which points to no or very little void formation. This differs considerably from the results of Zhurkov et al [14] who found a high increase of the intensity over the entire angular range for films of oriented polyethylene strained to breakage. Similar results during straining were observed for unoriented polyoxymethylene [15,16] and hard elastic fibres [17,18] and were attributed to extensive void formation.…”
Section: Saxs Of Mechanically Stressed Gel-spun Polyethylene Fibrescontrasting
confidence: 99%
See 1 more Smart Citation
“…Only a very small increase of the equatorial intensity is observed limited to the smaller angles which points to no or very little void formation. This differs considerably from the results of Zhurkov et al [14] who found a high increase of the intensity over the entire angular range for films of oriented polyethylene strained to breakage. Similar results during straining were observed for unoriented polyoxymethylene [15,16] and hard elastic fibres [17,18] and were attributed to extensive void formation.…”
Section: Saxs Of Mechanically Stressed Gel-spun Polyethylene Fibrescontrasting
confidence: 99%
“…Another type of void is found in crystalline polymer fibres/films subjected to mechanical stresses. Examples are oriented polyethylene [14], unoriented polyoxymethylene [15,16] and hard elastic fibres [17,18]. These voids are more or less rotational ellipsoids with the smallest axis parallel to the draw direction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper for example [Parpal, et aL (1997)] proposes a model to describe a Wde range of experimental observations that were described in an earlier paper [Dang, et aL(1996)]. In this paper they state "Ahe proposed model described relies on simple thermodynamic arguments (Crine 1990), on part of the free-volume breakdovm theory of Artbauer (1996) on the formation of sub-micron sized cavities observed by Zhurkov (1972) during the, mechanical ageing of polymers and on the molecular ageing model of Crine and Vijh (1985) 3-34 3.3. The Electro-mechanical Model of Breakdown.…”
Section: -33mentioning
confidence: 99%
“…Electrons can then move without scattering within the submicrocavities and this may lead to further degradation. The formation of free radicals and end-groups of scission molecules formed in polyethylene, polypropylene and polycaprolactam under axial tension was already investigated many years ago, and their asso-ciation with sub-microcrack generation in stressed polymers was well established (Zhurkov et al 1972). The number of scission chains may reach 10 19 cm -3 , three orders of magnitude larger than the number of free radicals detected in the stressed polymer, which is in turn about of the same order of magnitude as the detected sub-microcracks.…”
Section: Electrostatic Phenomenamentioning
confidence: 99%